RELASI MODAL SOSIAL DAN DAYA TAHANUSAHA INDUSTRI KECIL DI KABUPATENPROBOLINGGO - Ahmad Sauqi; Amien Pudjanarso (RELASI : JURNAL EKONOMI, 2015)
Small industries developed in the hope of reducing the amount of productive forces which will flow into the city, so that the rural economy will move and create jobs and increase income for the community. Small industries experiencing positive growth due to: First, the small business sector is able to survive in the face of the global economic crisis that is relatively unaffected, even still able to grow. Secondly, there is the possibility of large and medium-sized business sector who drowned in floods global economic crisis which eventually shifting economic activity to small businesses. Given the tremendous contribution in the development of small industries that spur economic growth, the government and the community should work to support and maintain it. The ability of small industries to survive and contribute actively to the economic growth due to the effort required by the public for their survival. To determine the forms of social capital in economic activity of small industries that affect the resilience of the business, the process of transformation of social capital into economic capital and social capital design that is ideal for industrial development. This study, using a qualitative approach with domain approach and taxonomy.